The Historical Development of Primary and Islamic Education in Indonesia: From Empire to Reform Era - Muh Syauqi Malik; Kartika Dwi Astuti; Vit Ardhyantama; Muhammad Imaduddin; Hana Andriningrum; Helda Kusuma Wardani (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
The phrase